2015
DOI: 10.3201/eid2107.141888
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patients under Investigation for MERS-CoV Infection, United States, January 2013–October 2014

Abstract: Middle East respiratory syndrome (MERS) cases continue to be reported from the Middle East. Evaluation and testing of patients under investigation (PUIs) for MERS are recommended. In 2013–2014, two imported cases were detected among 490 US PUIs. Continued awareness is needed for early case detection and implementation of infection control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…More viruses than bacteria were detected in both children and adults, and C T values were earlier for almost all pathogens in high-quality sputum than in was not included in the original viral testing algorithm. This correlates to other studies that demonstrated a preference for LRT specimens (8,(14)(15)(16). The observed increased detection of bacteria in high-quality sputum for adults compared with that for children may be, in part, because the adult TAC had four extra bacterial targets (Acinetobacter baumannii, E. coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa) compared with those of the pediatric card; these 4 targets accounted for approximately 20% of the bacterial detections in adults.…”
Section: Discussionsupporting
confidence: 87%
“…More viruses than bacteria were detected in both children and adults, and C T values were earlier for almost all pathogens in high-quality sputum than in was not included in the original viral testing algorithm. This correlates to other studies that demonstrated a preference for LRT specimens (8,(14)(15)(16). The observed increased detection of bacteria in high-quality sputum for adults compared with that for children may be, in part, because the adult TAC had four extra bacterial targets (Acinetobacter baumannii, E. coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa) compared with those of the pediatric card; these 4 targets accounted for approximately 20% of the bacterial detections in adults.…”
Section: Discussionsupporting
confidence: 87%
“…MERS was first recognized in 2012, and as of November 3, 2016, Saudi Arabia has reported 80.9% of the cases reported worldwide ( 11 ); this distinction may be partly due to the country’s robust implementation of surveillance practices and the ready availability of testing, which is facilitated by HESN. We found few other published descriptions of surveillance practices for MERS-CoV ( 12 , 13 ). …”
Section: Discussionmentioning
confidence: 92%
“…Similarly, in a small study in Saudi Arabia, influenza viruses were detected in 16% of 182 patients [29]. Similarly, among a small study of 52 suspected MERS cases in the United States of America, Influenza was the most commonly (35%) identified respiratory agent [41] and another study found influenza A and B in 11% of 296 investigated patients [26]. Thus, it is important to test for common respiratory pathogens such as influenza viruses and it should be noted that identification of a respiratory pathogen should not exclude MERS-CoV testing [42].…”
Section: Discussionmentioning
confidence: 83%
“…The study showed only 384 (0.7%) MERS-CoV positive cases [25]. In a study in the United States, two (0.4%) imported cases were detected among 490 patients-under investigation in 2013-2014 [26]. In a surveillance study of 1586 unique persons from the United Arab Emirates between January 1, 2013and April 17, 2014, 41 (3%) tested positive for MERS-CoV infection [27].…”
Section: Discussionmentioning
confidence: 93%